Evaluasi Kualitas Website Layanan E-Government Disdukcapil Kabupaten Kotawaringin Timur Menggunakan Metode Webqual 4.0 - Nadia Tiara Rahman; Agung Purwanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
E-government is the government's performance to support service and administrative processes in disseminating information to the public to be more efficient and effective. The service website for the Population and Civil Registration Service is an e-government website located in East Kotawaringin with the address https://disdukcapil.kotimkab.go.id/. The website has been developed in 2022 and has not yet been evaluated. To meet the quality requirements of high-quality websites with usability, information and quality of service. In the evaluation process, the researcher employed the Webqual 4.0 method which has three dimensions of measuring website quality including usability, information quality, and service interaction quality. The research was conducted by distributing questionnaires using purposive sampling technique to the users who had used the website of the Department of Population and Civil Registration, and the study involved 100 respondents. The research could be concluded partially with a significant level of test results less than 0.05 so that the independent variable had an influence on the dependent variable. The results of the study showed that there were two dimensions that had a positive and significant effect on the users’ satisfaction, namely the quality of usability with a significant value of 0.001 < 0.05 and Tcount > Ttable (3.343 > 1.98498) and service quality with a significant value of 0.000 < 0.05 and Tcount > T table (8.410 > 1.98498), while the dimension that did not have a positive and significant effect on the users’ satisfaction was the quality of information with a significant value of 0.606 > 0.05 and Tcount < T table (0.517 < 1.98498).